Rattus norvegicus ... - Jo, Yeong-Seok; Baccus, John T.; Koprowski, John L. (Zenodo, 2018)
Rattus norvegicus (Berkenhout, 1769) —Brown Rat, common rat, Norway rat Mus norvegicus Berkenhout, 1769 p.5; Type locality- United Kingdom. M. caraco Pallas, 1778 p.91; Type locality- China and far eastern Siberia. Epimys norvegicus caraco: Sowerby, 1923 p.154. Rattus norvegicus caraco: Vinogradov & Obolensky, 1927 p.237; Won, 1958 p.449; Jones & Johnson, 1965 p.389; Won, 1967 p.248. R. norvegicus: Kishida & Mori, 1931 p.378; Won, 1958 p.448; Won, 1967 p.239; Won, 1968 p.172; Yoon, 1992 p.85; Han, 1994 p.47; Won & Smith, 1999 p.27; Han, 2004c p.118. R. norvegicus norvegicus: Kuroda, 1938 p.69; Won, 1968 p.173. Range: The brown rat is commensal everywhere people live on the Korean Peninsula and associated islands (Fig. 124). Remarks: Corbet (1978) noted that the common rat, Rattus norvegicus, had an extensive distribution in the world and recognized two subspecies (R. norvegicus norvegicus in the western Palearctic and R. norvegicus caraco in eastern Asia). Won (1967) reported two subspecies ... : Published as part of Jo, Yeong-Seok, Baccus, John T. & Koprowski, John L., 2018, Mammals of Korea: a review of their taxonomy, distribution and conservation status, pp. 1-216 in Zootaxa 4522 (1) on pages 182-183, DOI: 10.11646/zootaxa.4522.1.1, http://zenodo.org/record/2610198 ...